A/R/T-Candidates Explore Intersectional Identities Through Art. (3rd July 2019) - Baker, J. Scott; Bjork, Frankie; Bley, Elyse; Eckhoff, Elizabeth; Hubing, Elizabeth
Abstract : Teaching diversity and social justice can be difficult when working with teacher candidates (TCs) from primarily homogenous areas, with little to no exposure to pluralistic realities. In multicultural classes, TCs often struggle to understand intersections of race, gender, orientation, socioeconomic levels, religion, ability, and citizenship. In this article, an educational studies professor and four undergraduate students discuss their methodological use of Artist/Researcher/Teacher (a/r/tography) to introduce intersectionality to young students in the classroom. The article discusses a/r/tography as a method in teacher education and provides arts-based examples of how intersectionality can be taught in the PK–12 school system.